Protective Effect of an Inoculum of Lactic Acid Bacteria from Bovine Origin Against Salmonella Serotype Dublin in the Intestinal Tract of Mice - Frizzo, Laureano Sebastian (2010)
The purpose of this study was to determine the capacitty of an inoculum of lactic acid bacteria (LAB) of bovine origin-constituted by lactobacillus casei DSPV 318T, lactobacillus salivarius DSPV 315T and pediococcus acidilactici DSPV 006T containing about 10(9) cfu dose of each one ot the strains to inhibit in vivo the salmonella serotype dublin DSPV 595T effects and reduce the patologic consequences in a conventional group of mice experimentally challenged with a 2.5 x 10(5) cfu dosed of the pathogen bacteria.